EMPOWERING COMMUNITIES: ELECTRICAL ENGINEERING SERVICE INITIATIVES BY UKI TORAJA AND INTERNATIONAL STUDENTS - Pineng, Martina; Ambabung, Yusri (Jurnal Literasiologi, 2024)
The Electrical Engineering Service Initiatives at UKI Toraja represent a vital intersection of education and community empowerment. This program, conducted from June to July 2024, engaged both local and international students in hands-on workshops addressing electrical systems, renewable energy, and safety protocols. Utilizing a mixed-methods approach, the initiative evaluated participant knowledge and satisfaction through surveys and collaborative projects, such as solar panel installations and electrical safety demonstrations. Results indicated a significant increase in student confidence and community understanding of electrical safety, with confidence in engineering principles rising from 45% to 85% among participants. Feedback from community members highlighted improved knowledge of energy efficiency, reinforcing the initiative's impact on community resilience. These findings underscore the importance of experiential learning and cultural exchange in engineering education, promoting not only technical skill development but also stronger community ties and social responsibility. Future efforts should prioritize expanding outreach and innovative educational methodologies to deepen these impacts.